Active Nanointerface‐Assisted Co‐Assembly to Yolk–Shell Au@Ordered Mesoporous Carbon Nanospheres. Issue 2 (4th December 2019) - Zhang, Weicai; Peng, Jing; Zheng, Mingtao; Dong, Hanwu; Hu, Hang; Xiao, Yong; Liu, Yingliang; Liang, Yeru
Abstract: Assembling of well‐orientated mesopores and 0D substance into an orchestrate architecture for constructing advanced carbon‐based composites is highly attractive. Currently, this nanofabrication method is facing challenges, because of the difficulty in the co‐assembly of the building blocks is very hard to perform onto a high‐curvature and heterogeneous 0D substrate. Here, an efficient active nanointerface‐assisted co‐assembly approach for design and fabrication of a novel class of yolk–shell Au@ordered mesoporous carbon nanosphere is reported. The key point to this preparation strategy is construction of reactive aldehyde functional groups on the surface of Au@SiO2 nanospheres, which can react with the carbon source to in situ form a stable covalent bond at their nanointerface. The as‐synthesized yolk–shell Au@ordered mesoporous carbon nanosphere not only exhibits uniform spherical morphology and robust porosity but also possesses a totally new ordered mesoporous and fast permeable shell structure, providing a chance for greatly broadening their application scope. Abstract : An efficient active nanointerface‐assisted co‐assembly approach is developed for design and fabrication of a novel class of yolk–shell Au@ordered mesoporous carbon nanospheres. The key point to this preparation strategy is construction of reactive aldehyde functional groups on the surface of Au@SiO2 nanospheres, which can react with the carbon source to in situ form a stable covalent bond at their nanointerface.